Antiobesogenic Potential of Seaweed Dulse (Palmaria palmata) in High-fat Fed C57BL/6 J Mice (P21-014-19). (13th June 2019) - Mendez, Rufa; Miranda, Cristobal; Armour, Courtney; Sharpton, Thomas; Stevens, Jan Frederik; Kwon, Jung
Abstract: Objectives: The growing obesity challenge around the world continues to warrant interventions that could mitigate disease onset and progression. This study aimed to evaluate the potential of seaweed supplementation using dulse ( Palmaria palmata ) and wakame ( Undaria pinnatifida ), in improving caloric management and insulin resistance, and mitigating inflammation and gut microbiome shifts in diet-induced obesity in C57BL/6 J mice. Methods: Twenty-four individually-caged C57BL/6 J mice were fed ad libitum with a high-fat diet (HFD) with and without seaweed inclusion, and another 8 mice for low-fat control ( n = 8). Freeze-dried dulse and wakame were incorporated in the test diets at 5% inclusion level. Glucose tolerance test was performed during week 4 to assess insulin resistance state of test animals. After 9 weeks, fresh fecal samples were collected from all 32 mice prior to necropsy. These were used for the gut microbiome analysis using MiSeq. Fecal triglyceride levels were determined using Infinity Triglycerides Kit while plasma Monocyte Chemoattractant Protein-1 (MCP-1) was quantified using ELISA. Results: Despite higher feed intake, dulse-fed mice had lower feed efficiency, indicating less weight gain from same amount of diet. This group also showed improved early-phase insulin response compared to HFD and wakame-fed groups. Plasma inflammatory marker MCP-1 levels were also significantly reduced in dulse-fed mice. While liver triglyceride levels were not affected with the dietary inclusion, fecal samples showed that there was higher lipid being excreted in dulse-fed group. This suggests that caloric excess and inflammatory progression may have been mitigated by increased lipid excretion in the feces. Gut microbiome analysis showed that dulse-fed mice retained microflora composition that is comparable to those fed with low-fat diet. Conclusions: Our work reveals that dulse supplementation improved obesity and associated metabolic parameters by increasing lipid excretion, improving early-phase insulin response, and mitigating both inflammation and gut microbiome shifts associated with HFD, more effectively than wakame. These provide initial evidences that dietary inclusion of dulse holds therapeutic promise in mitigating diet-induced obesity. Funding Sources: Oregon State University Agricultural Research Foundation. Supporting Tables, Images and/or Graphs: